Ecological Justice for Timbulsloko: A Disaster Jurisprudence Approach - Dirgantara, Nibras Cahya; Maharani, Yusmita; Nada, Rahma Qothrun; Hidayatullah, Ahmad Fauzan (TEMALI : Jurnal Pembangunan Sosial, 2024)
Ecological justice is a concept that emerged in the field of disaster fiqh which emphasizes the importance of fair and equitable treatment of the environment. This article will explain how to apply disaster fiqh to understand and overcome ecological justice issues. The sinking of Timbulsloko is a real consequence of global climate change, often affecting the most vulnerable communities with literature and field observation methods. This article will also discuss the importance of the role of local communities in driving actions that support ecological justice. This includes raising awareness about climate change, mobilizing community support, and working with government and non-government to find sustainable solutions. In Timbulsloko Village, the main causes of land subsidence are geographical factors and continuous coastal erosion. Damage to infrastructure, infiltration of seawater into inland areas, and decreased agricultural productivity are impacts that have been felt today. In addition, this phenomenon has a significant impact on local economies, social welfare, and environmental sustainability. To understand the impact of land subsidence on residents' daily lives, the study included field surveys, analysis of geological data, and conducting interviews with local communities. Land subsidence in Timbulsloko Village is a complex challenge that requires special attention. With this research, readers can increase their understanding of the source of the problem and effective solutions.